Strategi Pengembangan Wilayah Agritourism di Pegunungan Menoreh Berbasis Pemberdayaan Komunitas - Tinton Ramadhan; Anjar Dwi Astono; Naik Henokh Parmenas (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study intends to obtain an effective and efficient strategy in the development of agritourism areas based on community empowerment. This study used a qualitative approach with six sources consisting of groups leaders of tourism enthusiasts, the members and representatives from the government. The analysis used in this research is SWOT with content analysis techniques IFAS, EFAS, and SFAS. The findings in this study indicate that there is still a very large potential for tourism, especially related to non-mainstream tourism such as cultural tourism, educational tourism and also religion tourism. The suggestion that can be given in this research is that there is a need for penta helix synergy in this community-based agritourism development strategy.